1971
DOI: 10.1073/pnas.68.6.1178
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cytokinin-Independent Tobacco Tissues by Substituted Fluorenes

Abstract: Two morphactins and three aminofluorenes initiated the formation of compact tissue nodules in hormone-dependent tobacco callus cultures. These nodules, upon subculture, behaved like partially transformed plant tumors. They grew on cytokinin-free media, while control callus and nonnodule tissue still required an exogenous cytokinin source. The data indicate that substituted fluorenes, including carcinogenic aminofluorenes, can cause a neoplastic growth response in cultured tobacco tissues. Of particular interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1973
1973
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Under certain conditions (Bednar and Linsmaier-Bednar, 1971;Syono and Fujita, 1994) or after prolonged periods of time in culture, some callus acquires the capability to grow in the absence of auxin and/or eytokinin. They become habituated (Gautheret, 1942;Meins, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Under certain conditions (Bednar and Linsmaier-Bednar, 1971;Syono and Fujita, 1994) or after prolonged periods of time in culture, some callus acquires the capability to grow in the absence of auxin and/or eytokinin. They become habituated (Gautheret, 1942;Meins, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Using the Oncotest [2] for the screening of carcinogenic compounds, we have shown that carcinogens strongly stimulate in vitro cancer DNA synthesis, but only slightly stim ulate normal DNA synthesis. Low concentra tions of carcinogens can also stimulate the multiplication of cancer cells in animals [1,3] and plants [5,20]. On the other hand, it has been reported that actinomycin D [21] and tumor-promoting agents such as phorbol derivatives induce terminal differentiation in promyclocytic leukemia cells [18,21] when used at very low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In order to account for enhanced in vitro cancer DNA synthesis [2] and accelerated multiplication of vegetable [5,20] and mam malian [1. 3, 21] cancer cells in the presence of carcinogens, anticancer drugs or various other compounds such as DMSO, croton oil and steroids, we attempted to establish possi ble correlations between in vitro cancer DNA synthesis, in vivo cancer cell multiplication and in vitro DNA strand separation cata lyzed by the above compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The induction of nitrate reductase was blocked by cycloheximide, puromycin, and actinomycin D in the presence of any one of the inducing agents (Table 1). DISCUSSION Autonomous growth has been shown in tissues transformed by bacteria (22)(23)(24)(25)(26), viruses (27,28), chemicals (29)(30)(31), and genetic factors (32)(33)(34). The present investigation established that y-irradiation can also induce autonomous growth in Haworthia callus.…”
Section: Resultsmentioning
confidence: 99%